Community Empowerment Through Amil School For The Enhancement of Productive Zakat Management - Makhrus, M; Hasan, Ibnu; Budi Santoso, Selamet Eko (CV. Inara, 2023)
Various elements of society and the government are now concerned with the professional and institutional administration of zakat so that it may have a systemic effect on society, namely the establishment of an independent and prosperous society. This article's purpose is to provide a comprehensive picture of community empowerment through amil schools and the administration of productive zakat. The method utilized in this activity is training through the provision of two-part material on the law of zakat and community empowerment. Community service activities in the form of productive zakat management training through community empowerment were avidly attended by delegates from service offices and recipients of partner scholarships for this activity, as demonstrated by the results of this activity. Partners carry out the productive zakat program through community empowerment, which is dispersed across multiple program areas, including economics, education, social, health, and calamity, and has a long-term impact through community empowerment activities. Participants can increase their knowledge, experience, and perspectives on the significance of productive zakat management as a result of this activity, as productive zakat management in the form of community empowerment is able to reduce poverty levels in society.